If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 5 = -22 Reorder the terms: 5 + -1x = -22 Solving 5 + -1x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = -22 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -22 + -5 -1x = -22 + -5 Combine like terms: -22 + -5 = -27 -1x = -27 Divide each side by '-1'. x = 27 Simplifying x = 27
| 9m^2-15m^3= | | 6x(4x+5)=0 | | 6(x+9)+x=7(-3-x) | | 9x^2-4x+4=-16x | | x+8.75=14.5 | | y^2+10=0 | | 4x+1-3=26 | | 6(x-men)+10=2(3x-4) | | 8y+6=78 | | 14x=0 | | -4(x+2)+5x=15 | | 5z+z=5z-2 | | ln(x)=3 | | 14.73=-24.23+b | | -x+8=28 | | -5+3(6+7n)= | | 65x+y=85 | | 3=x*2 | | r^2-9r-22=0 | | 16s^2-25=0 | | log(2x-11)-log(x-4)=1 | | 65x+x=85 | | r^2-2x-15=0 | | 4x^2-1x+5=0 | | 8x+13=4x+5 | | (2x)+(x+20)=180 | | 3x+6=201 | | x^2-7x=x(7+x) | | 2(a+3)=2*2*2*2*2+6 | | 4y^2+23y+28= | | x+4(x+2)=28 | | x^2+2x-875=0 |